Maine Sea Grant and the Humanities: Marine Science (and History and Art) for Maine People - Schmitt, Catherine (Maine Policy Review, 2015)
Sea Grant works at the boundary of science and society, with a research portfolio dedicated to applied science. Catherine Schmitt discusses how Maine Sea Grant addresses questions that are relevant to Maine communities and communicates this relevance by incorporating the humanities into its work with Maine’s coastal communities.